Zakat-based urban farming: A tool for poverty alleviation, community empowerment, financial inclusion, and food security - Kinan Salim; Baharom Abdul Hamid; Ziyaad Mahomed; Wiaam Hassan (Review of Islamic Social Finance and Entrepreneurship)
Purpose – This study introduces a zakat-based model aimed at poverty reduction and enhancing food security in urban settings. Drawing upon the principles of Islamic social finance, the model integrates urban farming with the utilization of zakat, charity, and corporate social responsibility funds, offering sustainable financial avenues for disadvantaged individuals and social enterprises. The primary objective of this research is to design and pilot test a practical model that not only generates consistent financial income, but also bolsters food security and advances financial inclusion. Methodology – This study reviews various models that have used Zakat funds for economic empowerment, conduct interviews, and hold focus group discussions. It proposes a zakat-based urban farming model for poverty alleviation and community empowerment using the theory of change. In collaboration with a leading Islamic bank in Malaysia, the model was pilot tested across selected residential communities in Malaysia. Finding – The research findings demonstrated positive impacts both at the individual participant level and within the broader community. Serving as a replicable blueprint, this project envisions the transformation of urban spaces into productive landscapes, thereby ensuring sustainable livelihood, amplifying food security, and promoting financial inclusion. Implication – Through this Zakat-based approach, the research underscores the profound impact of urban farming in catalyzing socio-economic change and advancing efforts towards poverty alleviation. Originality – No previous research has introduced and pilot-tested Zakat-based urban farming solutions for Islamic financial institutions as a tool for Poverty Alleviation and financial inclusion